Malignant eccrine poroma of the vulva: An intriguing case of a rare tumor at an unusual site - Pranshu Mishra; Sumit Sen; Neha Sharma; Debasish Sen (Wolters Kluwer Medknow Publications, 2016)
Malignant eccrine poroma is a rare malignancy of the eccrine sweat glands, occurring most frequently on the lower extremities. It affects both sexes equally usually in the 6 th to 7 th decade of life. Metastasis to regional lymph nodes may occur in 20% that may be fatal in 60% cases. Its aggressive nature, rarity of occurrence, and unusual presentations make it very important to be evaluated properly by the clinician. We hereby report a case of a 75-year-old female presenting with two exophytic tumors over her vulva with local extension. On histopathological examination, it was diagnosed as malignant eccrine poroma. On magnetic resonance imaging of the pelvic region, metastatic extension in regional lymph nodes was found. She was treated by radical vulvectomy with bilateral inguinal and femoral lymph node dissection followed by radiotherapy.